MAPPING THE HIGH SCHOOL OR EQUIVALENT COUNTRY STATUS IN URBAN AREAS MERANGIN DISTRICT OF JAMBI - Pratami, Melisya - (STKIP PGRI Sumbar, 2014)
This study aims to mappng the high school equivalent country status in urban areaMerangin District Jambi province and access road to High School (SMA) or equivalent in UrbanAreas Merangin DistrictThis type of research is descriptive quantitative. The population in this study are all stateschool equivalent of high school in an urban area Merangin District. Samples were taken bypurposive random sampling technique ie sampling technique deliberately or randomly inaccordance with the requirements of the sample. Analysis using spatial analysis and descriptiveanalysisResults of the study found that: 1) Senior High School (SMA) or equivalent in UrbanAreas Merangin district, where there are four high schools (SMA) or equivalent in urban areasMerangin district lies in a district that is urban area in the district is sub-districts Bangko Meranginand (2) the accessibility of the road to High School (SMA) or equivalent in Urban Areas Merangindistrict, road distance student house with generally <25 m, the houses on the flat, the averageclosest distance> 2 km, the general type of ordinary asphalt , the type of transportation that mostmotorcycles, the frequency of passing the house 6-10 / day. Barriers experienced by students isschool so far incurred costs generally> Rp 15,000 / day